Linear-Complexity H2-Based Direct Sparse Solver for Electromagnetic and Multiphysics Analysis - Ma, Miaomiao; Jiao, Dan (Digest - IEEE Antennas and Propagation Society. International Symposium (1995), 2019)
A fast nested direct matrix solution is developed for solving the sparse matrices resulting from electromagnetic and multiphysics analysis in linear complexity. In this solver, we accelerate all dense matrix computations underlying the state-of-the-art multifrontal direct solver by developing fast H 2 -based algorithms. Each computation is performed on small matrices of rank size, which is also the rank of the separator instead of the rank of the original 3-D problem. Direct solution of millions of unknowns arising from a finite-element based analysis is obtained in a few minutes on a single CPU core.